Challenges associated with the synthesis of unusual O-Carboxamido Stilbenes by the Heck Protocol: intriguing substituent effects, their toxicological and chemopreventive implications - Ariffin, Azhar; Thomas, N.F.; Kee, C.H.; Awang, K.; Takeya, K.; Morita, H.; Hussain, S.I.; Chan, K.M.; Weber, J.F.F.; Wood, P.J.; Threadgill, M.D.; Lim, C.G.; et al. (2010)
The syntheses of fourteen unusual o-carboxamido stilbenes by the Heck protocol revealed surprising complexity related to intriguing substituent effects with mechanistic implications. The unexpected cytotoxic and chemopreventive properties also seem to be substituent dependent. For example, although stilbene 15d (with a 4-methoxy substituent) showed cytotoxicity on HT29 colon cancer cells with an IC50 of 4.9 mu M, the 3,4-dimethoxy derivative (15c) is inactive. It is interesting to observe that the 3,5-dimethoxy derivative (15e) showed remarkable chemopreventive activity in WRL-68 fetal hepatocytes, surpassing the gold standard, resveratrol. The resveratrol concentration needed to be 5 times higher than that of 15e to produce comparable elevation of NQO1.